1999
DOI: 10.1007/s004120050357
|View full text |Cite
|
Sign up to set email alerts
|

Functional compartmentalization of the nucleus in the budding yeast Saccharomyces cerevisiae

Abstract: By combining cryofixation and cryosubstitution in a structural and functional analysis of the nucleus of Saccharomyces cerevisiae, we identified morphological subcompartments in the nucleolus. These were similar to those of nucleoli of higher eukaryotes, such as the fibrillar centre (FC), the dense fibrillar component (DFC) and the granular component (GC). In situ hybridization and immunocytochemistry revealed RNA polymerase I and proteins involved in early steps of ribosomal maturation along the DFC, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 63 publications
1
49
0
2
Order By: Relevance
“…Previous studies have indicated that pre-tRNAs and processing complexes may be distributed between nucleolar and nonnucleolar loci (25,45). However, electron microscopic localization of a polymerase III subunit in S. cerevisiae failed to find a significant concentration of the protein in the nucleolus, suggesting that the majority of polymerase III is not nucleolar (32). In this study we also did not find evidence that tRNA genes, the previously identified major chromosomal target of Ty3 integration, are generally localized to the nucleolus.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have indicated that pre-tRNAs and processing complexes may be distributed between nucleolar and nonnucleolar loci (25,45). However, electron microscopic localization of a polymerase III subunit in S. cerevisiae failed to find a significant concentration of the protein in the nucleolus, suggesting that the majority of polymerase III is not nucleolar (32). In this study we also did not find evidence that tRNA genes, the previously identified major chromosomal target of Ty3 integration, are generally localized to the nucleolus.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have suggested a direct link between other pre-rRNA processing factors and RNA polymerase I. The U14 and U3 snoRNAs and the H/ACA Cotranscriptional rRNA processing www.rnajournal.org snoRNP protein Gar1p localize in the dense fibrillar component (Lazdins et al 1997;Leger-Silvestre et al 1999), the probable site of transcription by RNA polymerase I (Hozak et al 1994;Jackson and Cook 1995;Lazdins et al 1997;Mosgoeller et al 1998). In addition, the nucleolar processing factor Nop1p colocalizes with RNA polymerase I in mouse embryos (Cuadros-Fernandez and Esponda 1996) and with nascent rRNA transcripts (Garcia-Blanco et al 1995).…”
Section: A Cotranscriptional Model For Pre-rrna Processing At the 3 Ementioning
confidence: 99%
“…The nuclear export of both the large and small ribosomal subunits has been shown to be dependent, at least indirectly, on the Ran-GTPase cycle and the exportin CRM1, and it is likely that CRM1-mediated export of 60S subunits requires the adaptor protein NMD3 (Moy and Silver, 1999;Ho et al, 2000;Gadal et al, 2001;Thomas and Kutay, 2003;Trotta et al, 2003). In situ hybridization experiments in fission yeast have indicated that rRNA may accumulate along short tracks when near the nuclear pores but nonetheless appears to exit from all the pores, not just those near the nucleolus (Léger-Silvestre et al, 1999). In situ hybridization studies in mammalian cells have primarily addressed the distribution of rRNA within the nucleolus (Huang, 2002) rather than the routes of extranucleolar rRNA traffic, because although high signal representing rRNA is routinely detected in both the nucleolus and the cytoplasm, nucleoplasmic signal which might represent ribosomes moving to the nuclear periphery is not easily detectable by in situ hybridization (PuvionDutilleul et al, 1991;Lazdins et al, 1997; J.C.R.…”
Section: Introductionmentioning
confidence: 99%